Comparison of Dividend Discount Model With Free Cash Flow To Firms For Valuation of Banking Stocks Listed in Jakarta Islamic Index (JII) Period 2016-2020 - Hendra Dukalang; Wiwin Koni; Nhayu Cahya Mokoagow (UIN Mataram, 2021)
This study aims to find out and analyze the fair value of stocks and stock conditions in banking companies using dividend discount model (DDM) and free cash flow to firms (FCFF) during the 2016 – 2020 period. The population is in research in as many as 70 companies. Determination of samples with purposive sampling techniques, so that the samples obtained by 2 companies. The data used is secondary data and calculations by using Microsoft Excel 2016 application. The results showed that of the 2 banking companies listed in JII, bris and BTPS shares have different intrinsic values. Valuation Results using DDM show that the intrinsic value of BRIS Shares is in an Overvalued condition, for BTPS shares are undervalued. While the valuation result using FCFF obtained intrinsic value of BRIS shares is undervalued, for BTPS shares is in an Overvalued condition.